Age verification cards fail to fully prevent minors from accessing tobacco products. Issue 2 (21st October 2010) - Kanda, Hideyuki; Osaki, Yoneatsu; Ohida, Takashi; Kaneita, Yoshitaka; Munezawa, Takeshi
Abstract : Background: Proper age verification can prevent minors from accessing tobacco products. For this reason, electronic locking devices based on a proof-of age system utilising cards were installed in almost every tobacco vending machine across Japan and Germany to restrict sales to minors. Objective: We aimed to clarify the associations between amount smoked by high school students and the usage of age verification cards by conducting a nationwide cross-sectional survey of students in Japan. Methods: This survey was conducted in 2008. We asked high school students, aged 13–18 years, in Japan about their smoking behaviour, where they purchase cigarettes, if or if not they have used age verification cards, and if yes, how they obtained this card. Results: As the amount smoked increased, the prevalence of purchasing cigarettes from vending machines also rose for both males and females. The percentage of those with experience of using an age verification card was also higher among those who smoked more. Somebody outside of family was the top source of obtaining cards. Surprisingly, around 5% of males and females belonging to the group with highest smoking levels applied for cards themselves. Conclusions: Age verification cards cannot fully prevent minors from accessing tobacco products. These findings suggest that a total ban of tobacco vending machines, not an age verification system, is needed to prevent sales to minors.